Penerapan Model Student Facilitator And Explaining (SFAE) Terhadap peningkatan kemampuan berpikir kritis siswa pada subtema 3 di kelas V SD Negeri Lam Ura Aceh Besar - Maulidar Maulidar; Putry Julia; Rifaatul Mahmuzah (Jurnal Dedikasi Pendidikan, 2023)
The background of this research is the low critical thinking skills of students which affect the low learning completeness so that student scores tend to be below the KKM, namely 75. This study aims to determine the increase in students' critical thinking skills through the application of the Student Facilitator And Explaining (SFAE) model. This research uses a quantitative approach with the type of Pre-Experimental Research. The population in this research is 15 students. While the sampling technique is the entire population being sampled or the total sampling is 15 students of class V. The data collection technique is in the form of observation and tests. And data analysis techniques using the t-test formula. The results showed that the application of the SFAE model could improve students' critical thinking skills, because based on the t distribution list for the right side test at df 14 (α = 0.05) obtained t-table 2.144.Furthermore, the calculation of the price of t-count is 61.44 and the price of t-count> t-table or 61.44> 2.144. Thus the hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This can be seen clearly by the difference between students' critical thinking skills before applying the Student Facilitator And Explaining (SFAE) model (pre test) and after using the application of the Student Facilitator And Explaining (SFAE) model (post test) in sub-theme 3 in class V SD Negeri Lam Ura Aceh Besar.